(untitled) (Research, Society and Development, 2024)
Objective: to analyze and associate the quality of prenatal care offered to pregnant women with pre-eclampsia to maternal outcomes. Method: This observational study with a qualitative and quantitative approach evaluated the quality of prenatal care in pregnant women with pre-eclampsia. Data were collected through interviews, prenatal cards and electronic medical records. The quality of prenatal care was analyzed using the Kessner index adapted by Takeda through descriptive analysis. Non-categorical variables were subjected to statistical tests, such as chi-square, Pearson, Fisher, Mann-Whitney and multiple logistic regression. The study was approved by the Ethics Committee under number 67769123.1.0000.5201. Results: 72.1% of patients had inadequate prenatal care, they were 4.43 times more likely to develop pre-eclampsia with signs of severity (p=0.01), the use of acetyl salicylic acid and calcium had statistical significance regarding the classification of pre-eclampsia (p<0.001) and 75.3% had a high birth. Conclusion: The majority of pregnant women received inadequate prenatal care, associated with a significant increase in the probability of developing pre-eclampsia with signs of severity.